The Role of Lymph Node Dissection for Non-Metastatic Renal Cell Carcinoma: An Updated Systematic Review and Meta-Analysis - Shi, Xu; Feng, Dechao; Li, Dengxiong; Zhang, Facai; Wei, Wuran (Frontiers in Oncology, 2022)
INTRODUCTION: To compare the survival benefit of nephrectomy with or without lymph node dissection (LND) for non-metastatic, especially for high-risk renal cell carcinoma (RCC) patients by investigating different survival evaluation indicators. EVIDENCE ACQUISITION: Eligible studies were identified until September 2021, through common databases including PubMed, the Cochrane Library, Embase and China National Knowledge Infrastructure (CNKI) on RCC and LND without language restriction. Data analysis was performed through STATA version 16.0. EVIDENCE SYNTHESIS: 22 articles were included in this meta-analysis. For non-metastatic RCC, performing LND comitantly with nephrectomy did not change the overall survival (OS) of patients of all T stages [hazard ratio (HR)=1.10, 95%CI: 0.95-1.27] and also for T2+NxM0 patients (HR=0.88, 95%CI: 0.68-1.14) as well as for T3+NxM0 patients (HR=0.95, 95%CI: 0.61-1.50). At the same time, cumulative meta-analysis has shown that the survival benefit of LND has a significant declining trend since 1979. However, it is worth noting that the operation of LND presented as a risk factor for cancer specific survival (CSS) (HR=1.22, 95%CI: 1.05-1.43). CONCLUSIONS: Latest evidence indicated that LND might not be suitable for all non-metastatic RCC patients, especially in the current situation of various non-invasive examinations for judging lymph node metastasis and adjuvant treatments. On the contrary, excess LND could damage the survival of patients.